OUTCOME BASED LEARNING: AN ANALYSIS OF IMPACT ON ACADEMIC ACHIEVEMENT AMONG SCHOOL STUDENTS - Thote, Prashant; S, Gowri (International Journal of Research -GRANTHAALAYAH, 2020)
The present century belongs to Science and Technology. Scientific knowledge is valued across the globe and great emphasis is on scientific attitude towards all fields of life. The purpose of education of Science school is to lead the nation to collaborate and compete with rest of the world. The students face difficulty in studying Chemistry due to its abstract nature of concepts. To address this issue, students are taught solid state Chemistry by using computer-based models of unit cells and the crystal lattices. The present study is experimental in nature. Total 60 students participate in the study. Samples are distributed in two groups (study group and control group). Data is collected by using question paper. The Chemistry of solid state is taught to the experimental group by using model based on computer and control group is taught by using traditional chalk and board methodology. The instrument is validated by its content and is consulted by an expert. The instrument reliability of is analyzed by applying t-test. Result of the research reveals that the computer-based model on crystal lattices and unit cell is more effective than conventional model in learning and the academic achievement of the students in Chemistry. The t-test proves that the t-value 0.691 is substantial with p (p<0.05). Based on the findings of the present study the computer-based model of unit cell and crystal lattice is an effective teaching tool for learning and to improve the academic achievement in Chemistry.